ESTIMATION OF CURRENT STATUS OF FLORAL BIODIVERSITY AT M.J.B COLLEGE CAMPUS INDORE WITH SPECIAL REFERENCE TO MEDICINAL AND ORNAMENTAL PLANTS - Mahajan, Saroj; Gangrade, Anita (International Journal of Research -GRANTHAALAYAH, 2019)
The traditional knowledge started from Vedic Time (1000-5000B.C.) Our epics Ayurveda, Rigvade, Yagurveda were reported Plants used as a medicinal plant. These medicinal plants were used by Tribal people, villagers, Urban of India. The traditional knowledge of medicinal plants of Tribals are transferred from one gene ration to other generation. Plants have medicinal value too along with ornamental purpose. Indians have been using plants as medicines to treat many diseases like wounds healing, inflammation. The ancient science of Ayurveda and Yoga relied heavily on these plants to treat major conditions, from pain management to weight management and everything in between. The list of medicinal plants too long but some important which are present in our college campus are Aloevera, Awala, Hadjod, Tulsi, Giloy, Neem Arjun, Bel, Ashwagandha. The large numbers of plant i.e. plant vegetations enormous in the college campus which shows the biodiversity of college campus.